2008
DOI: 10.1097/hjh.0b013e3282fb81c8
|View full text |Cite
|
Sign up to set email alerts
|

Very low frequency blood pressure variability is modulated by myogenic vascular function and is reduced in stroke-prone rats

Abstract: Myogenic function affects very low frequency blood pressure variability in conscious rats and dogs. The smaller very low frequency blood pressure variability in stroke-prone spontaneously hypertensive rats compared with stroke-resistant spontaneously hypertensive rats suggests that impaired cerebrovascular myogenic function is reflected in reduced very low frequency blood pressure variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Over a decade ago, it had been suggested that the renin-angiotensin aldosterone system may contribute importantly to VLF BPV (7,20,21). Furthermore, studies from our laboratory demonstrated that VLF BPV depends on L-type Ca 2ϩ channels (16) and suggested that myogenic vascular function contributes significantly to VLF BPV (31). One importance of these findings is that cerebrovascular myogenic function normally protects the brain from hemorrhagic stroke and that a loss of myogenic vascular function [e.g., in chronic renal failure (15,18)] constitutes an important risk factor for hemorrhagic stroke (25,26).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Over a decade ago, it had been suggested that the renin-angiotensin aldosterone system may contribute importantly to VLF BPV (7,20,21). Furthermore, studies from our laboratory demonstrated that VLF BPV depends on L-type Ca 2ϩ channels (16) and suggested that myogenic vascular function contributes significantly to VLF BPV (31). One importance of these findings is that cerebrovascular myogenic function normally protects the brain from hemorrhagic stroke and that a loss of myogenic vascular function [e.g., in chronic renal failure (15,18)] constitutes an important risk factor for hemorrhagic stroke (25,26).…”
mentioning
confidence: 92%
“…Indeed, VLF BPV is reduced in stroke-prone spontaneously hypertensive rats compared with stroke-resistant spontaneously hypertensive rats (31). However, the concept that VLF BPV primarily reflects myogenic vascular function and/or autoregulation of blood flow and, therefore, predicts hemorrhagic stroke in subjects with reduced VLF BPV is currently not generally accepted (12).Specifically, a limitation of our laboratory's previous studies (16,31) was that the conclusion that myogenic vascular function contributes significantly to VLF BPV was based on experiments utilizing the L-type Ca 2ϩ channel blocker nifedipine. As pointed out in our laboratory's previous papers (16, 31), L-type Ca 2ϩ channels are also involved in the vascular actions of vasoactive substances, such as catecholamines.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Our choice to analyze DBP and its variability, in a previous work (2) and in this paper as well, is based on the relationship between the diastolic decay and TPR (27,31), and on the observation that DBP spectral power is mostly concentrated in the low-frequency (LF, ϳ0.1 Hz) band, i.e., the band of vasomotor and resistance fluctuations. Therefore, DBP was assumed to be specifically sensitive to vasomotor tone, and modulations in the LF band were assumed to reflect baroreflex-mediated regulation of vascular resistance, whereas autoregulation phenomena may be confined to slower oscillations, typical of the very low-frequency band (VLF; f Ͻ 0.04 Hz), as shown by Stauss et al (43). The choice of SBP as the input to the arterial baroreflex-related component of the model was consistent with typical approaches to the assessment of cardiac baroreflex, which use SBP as the input, since it is known to convey both the phasic and tonic dynamic features to which baroreceptors are sensitive, and heart rate or R-R as the output.…”
Section: Methodsmentioning
confidence: 99%
“…More recently the importance of BPV in prediction of risk of vascular events and in accounting for benefits of antihypertensive drugs, especially in prevention of stroke, was emphasized [5][6][7] . Multiple studies have investigated the roles of resting vascular tone changes, arterial pressure levels, the sympathetic nervous system, and vasoactive substances in the increased BPV after SAD [3,[8][9][10][11][12][13][14] . However, the definite mechanism by which BPV dramatically increase after SAD surgery is still unclear.…”
Section: Introductionmentioning
confidence: 99%